MENINGKATKAN KEMAMPUAN MENGENAL KATA MELALUI PERMAINAN KARTU KATA BERGAMBAR BERBENTUK JENDELA DI TAMAN KANAK-KANAK NEGERI PEMBINA LUBUK BEGALUNG PADANG - Yosmelia Yosmelia; Prima Aulia (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This study aims to improve the word recognition skill in public kindergarten Pembina Lubuk Begalung Padang. The type of the research that will be done is the class action research that is the observation of the activities in a class is occured purposely. The qualitative and quantitative data analysis technique uses percentage approach in order to get the result of the research. On the first cycle of the three meetings, The development of the word recognition skill has reached 44% and it does not fulfill the criteria of the minimal exhaustuvenes yet. On the second cycle in the research implementation three is very significant improvement in recognizing words that is 88% and it has reached the criteria of the minimal exhaustiveness. The result shows that the window-sahped picture word card game has been able to improve the enchancment of the word recognition in public kindergarten Pembina Lubuk Begalung Padang.